1998
DOI: 10.1002/(sici)1097-4679(199808)54:5<701::aid-jclp16>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Parent reports of sleep disturbances in stimulant-medicated children with attention-deficit hyperactivity disorder

Abstract: In a study of the severity of sleep disturbances in children with attention-deficit hyperactivity disorder (ADHD) who are taking stimulant medication, parents of 20 children diagnosed as having ADHD and on medication, 20 unmedicated children with some other psychiatric diagnosis (OPD), and 20 nonclinical control children responded to a 40-question structured interview to report the frequency of their children's sleep disturbances occurring during a 1-month interval. Parents of children in the ADHD group report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 19 publications
0
22
1
Order By: Relevance
“…Earlier studies that investigated the effects of stimulants on sleep have produced mixed results. Several studies reported a substantial number of complaints of sleep disturbance associated with single or multiple daily doses of MPH (Stein et al, 1996;Day and Abmayr, 1998;Corkum et al, 2008), whereas other studies found no such complaints (Kent et al, 1995). Results of studies using objective measures, including actigraphy and polysomnography, have also been inconsistent.…”
Section: Introductionmentioning
confidence: 79%
“…Earlier studies that investigated the effects of stimulants on sleep have produced mixed results. Several studies reported a substantial number of complaints of sleep disturbance associated with single or multiple daily doses of MPH (Stein et al, 1996;Day and Abmayr, 1998;Corkum et al, 2008), whereas other studies found no such complaints (Kent et al, 1995). Results of studies using objective measures, including actigraphy and polysomnography, have also been inconsistent.…”
Section: Introductionmentioning
confidence: 79%
“…8,24,25 Moreover, early school starting hours have been linked with shorter sleep duration and inattentiveness at school. 11 Contrasting findings also exist: longer mother-reported sleep duration was related to behavioral symptoms on Conner's ADHD scale.…”
Section: Discussionmentioning
confidence: 99%
“…This disorder persists into adolescence and young adulthood in 10% to 60% of affected individuals. 52 The relationship between sleep problems and ADHD in children has been examined in multiple studies, using a number of approaches, [53][54][55][56][57][58][59][60][61][62][63][64][65][66] but similar data in adolescents and adults are largely unavailable. Reviews of clinical complications of ADHD in adolescents include some anecdotal references to sleep disturbances, [67][68][69] but studies of childhood ADHD and sleep are rare and have included small numbers of subjects between 12 and 18 years of age.…”
Section: Sleep and Attention-deficit/hyperactivity Disorder In Adolesmentioning
confidence: 99%